Research on Regional Socio-Economic-Environmental Evaluation Based on Combined Objective Weight Method-Taking Sinan County of Guizhou Province as an Example - YU Hongmin; HE Linhong; LI Xinan; WANG Mengqi (Renmin Zhujiang, 2023)
With the high-quality development at the national level,the comprehensive evaluation of regional coordinated development has become a hot topic of concern,and the evaluation of regional coordinated development has evolved from a single evaluation to a comprehensive evaluation.There is a complex coupling relationship between regional society,economy,and environment.In order to achieve sustainable and coordinated regional development,a comprehensive evaluation system including nine secondary evaluation indicators and 22 tertiary evaluation indicators was constructed in terms of three dimensions:society,economy,and environment.According to the data of Sinan County in Guizhou Province from 2014 to 2018,the variation coefficient method,entropy weight method,and other methods were used to calculate the comprehensive weight of each indicator of the social-economic-environmental system.Then the coupling coordination degree was calculated,so as to provide a scientific basis for the sustainable development of the county.The results show that from 2014 to 2018,① the effect of environmental improvement is relatively lagging behind that of the other two systems and can be classified as a relatively lagging type of environment;② the development of the social subsystem first decreases and then increases,and it then decreases to the initial level,while the economic and environmental subsystems show a stable increasing trend;③ the coupling degree and coordinated development degree of the system show an increasing trend year by year,and the system is now on the verge of high coupling degree and dysfunctional development.